INVESTIGATION ON TEACHERS COMPETENCY ON USING ICT FOR TEACHING AND LEARNING MATHEMATICS AND SCIENCE SUBJECTS IN TANZANIAN SECONDARY SCHOOLS - Langoi, Sinyati; Deogratias, Emmanuel (International Online Journal of Education and Teaching, 2024)
This study focused on investigating teachers’ competence on using ICT in teaching and learning mathematics and science subjects in secondary schools in Morogoro municipality. The research employed a quantitative method with the use of the descriptive design. The study had objectives that are to examine the teacher’s ability to use the ICT tools, to show the relationship between the ICT tools and students’ performance and to find out the challenges that teachers face during the use of ICT in teaching and learning process. The study used a sample of two secondary schools of which 35 teachers were selected from each school making a total of 70 respondents, whereby the questionnaires were used to collect data and the data were analyzed using the SPSS method. It was found that many teachers have the ability to use the ICT tools in teaching, and that there is a significant relationship between teacher competency in the use of ICT in teaching and the students’ academic performance. It was also found that teachers face some challenges during the use of ICT tools in teaching including the poor infrastructure, the lack of expertise and capital problems. It was also found that the ways of overcoming them include improving the infrastructure, use of printed media as an alternative to the ICT tools as well as developing consistency of teachers. The study also recommends that the Ministry of Education, science and technology should ensure that all teachers train in ICT by introducing compulsory ICT courses to create the innovative model for teachers, sufficient facilities and resources should be provided and also professional development programs should be organized for teachers in order to develop ICT knowledge and competence.